The Role of Probiotic Therapy in Pediatric MASLD: Pathophysiological and Clinical Perspectives - Staszko, Natalia; Bała, Kamila; Bukowska, Małgorzata; Zbroniec, Jakub (Quality in Sport, 2026)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is currently the most common chronic liver disease in children, with its prevalence steadily increasing alongside the global epidemic of childhood obesity. Despite the growing scale of the problem, effective therapeutic strategies remain limited. Recently, an increasing evidence has highlighted the role of gut dysbiosis and gut-liver axis in the pathogenesis of MASLD, prompting interest in probiotics as a potential treatment. Available date indicate that probiotics may improve liver enzymes and reduce hepatic steatosis, suggesting their potential as an adjunctive therapy. Additional reported benefits include favorable modulation of appetite-regulating hormones (leptin, ghrelin), reductions in anti-peptidoglycan antibodies and increases in incretin hormone GLP-1. However, current date are constrained by substantial limitations, preventing definitive conclusions regarding probiotic efficacy. Therefore, further well-designed studies involving larger sample sizes, longer follow-up periods, and standardized assessment methods are required to fully determine the therapeutic value of probiotics in pediatric MASLD.